The Influence of Workload and Work-Life Balance on Organizational Performance Mediated by Motivation Among Employees of PT Bank Woori Saudara 1906 Tbk, Region III - Aviana, Elma; Widjanarko, Hendro; Wahyuni, Purbudi (CV. Strata Persada Academia, 2025)
This study examines the influence of workload and work-life balance on organizational performance, with motivation as a mediating variable, among employees of PT Bank Woori Saudara 1906 Tbk, Region III (Central Java and D.I. Yogyakarta). The research is motivated by fluctuating employee performance appraisals observed between 2020 and 2024, with a notable increase in employees rated “Poor” and persistently low ratings of “Very Good.” Drawing upon Self-Determination Theory and Work-Family Border Theory, this study highlights workload, work-life balance, and motivation as key factors shaping employee performance. A quantitative approach with a causal associative survey design was employed, using Likert-scale questionnaires distributed to all 124 employees as part of a census sample. Data were analyzed using Partial Least Squares (PLS) after conducting validity and reliability tests. The findings confirm that workload and work-life balance significantly affect organizational performance, both directly and indirectly through motivation. Properly managed workload and balanced personal-professional life contribute to higher focus, engagement, and productivity, while motivation acts as a critical psychological mechanism that enhances the positive effects of these factors.